Outcomes of Patients with Melioidosis Treated with Cotrimoxazole Alone for Eradication Therapy - Chusri, Sarunyou (The American Society of Tropical Medicine and Hygiene, 2012)
We retrospectively reviewed a 10-year experience of administration of cotrimoxazole alone in 31 patients compared with 109 patients who received conventional eradication therapy (cotrimoxazole plus doxycycline). The baseline characteristics, the clinical manifestations, the initial intravenous antibiotic treatments, and the mean duration of eradication therapy between the two groups were similar. The culture-confirmed recurrences among the patients who received cotrimoxazole alone and those who received the conventional regimen were not significantly different (1/31 [3.2%] versus 5/109 [4.5% odds ratio = 0.69 [95% confidence interval [CI] = 0.08–6.17]). Gastrointestinal side effects were more common among the conventional regimen group (28/109 [25.7%] versus 2/31 [6.5%], P = 0.02) and the proportion of patients who could complete at least 20 weeks of therapy without having switched to the other regimen was significantly lower (91/109 [83.5%] versus 31/31 [100.0%] P = 0.01). Cotrimoxazole alone is as effective as and better tolerated than cotrimoxazole plus doxycycline for the eradication treatment of melioidosis.